Goal-Oriented Evaluation of Educational Data Integration: Assessing Dapodik-SPMB Implementation in Indonesian Schools - Kasbijanto, Kasbijanto; Haq, Mohammad Syahidul; Amalia, Kaniati; Khamidi, Amrozi (Journal of Innovation and Research in Primary Education, 2025)
This study evaluated Dapodik integration effectiveness in the New Student Admission System (SPMB) at state junior high schools in Bojonegoro Regency, Indonesia, focusing on verification speed enhancement and data accuracy improvement. Employing a goal-oriented evaluation approach, the research utilized quantitative descriptive methods with 60 purposively sampled respondents comprising Dapodik operators, school SPMB committees, and district education office administrators. Data were collected through four-point Likert scale questionnaires (43 items across seven indicators), documentation checklists, and official SPMB records. Instrument validity was established through expert judgment (Aiken's V > 0.80) and construct validity testing (Pearson correlation), while reliability was confirmed via Cronbach's Alpha (> 0.70). Descriptive statistics and gap analysis were employed to assess objective achievement. Results demonstrated that verification speed achieved 85.94% goal realization (mean = 3.44, gap = +0.18), while data accuracy attained 82.96% (mean = 3.32, gap = +0.06), both exceeding achievement thresholds. The integration successfully reduced processing time, maintained schedule accuracy, and enhanced NISN verification and domicile compliance. However, persistent technical barriers (system downtime) and data-document mismatches indicated areas requiring improvement. The findings confirm that Dapodik-SPMB integration substantially achieves policy objectives while revealing that structural integration (efficiency) outperforms semantic integration (quality), underscoring the necessity of combining technological infrastructure with data governance protocols and operator capacity development for sustainable administrative excellence in educational systems.